Distribution and Growth in Open Economies: A Post-kaleckian Explanation - Velázquez Orihuela, Daniel (Universidad Pedagógica y Tecnológica de Colombia, 2023)
In this paper the framework proposed by Velázquez (2022) is expanded to analyze the bidirectional relationship between the economic growth and the functional income distribution in open economies. Two exchange regimes are analyzed: the fixed and floating exchange rates. It is shown that if growth is led by wage, growth and distribution paths are cyclic, regardless the exchange rate policies. On the other hand, if growth is led by profits and the exchange rate is flexible, then growth is steady and the profit sharing goes upwards. However, if in this scenario there is a fix exchange rate, the growth and distribution paths are cyclic.